2020
DOI: 10.1057/s41599-020-00654-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of stereotypes applied to women who publicly communicate their STEM work

Abstract: Gender biases and stereotypes are prevalent in science, technology, engineering and mathematics (STEM) fields, which can create obstacles for the attraction, retention and progression of girls and women to STEM studies and careers. There are many initiatives which are used to attempt to address these biases and stereotypes, including the use of visible role models. This study explores the perceptions of the stereotypes applied to female STEM professionals who publicly speak about their work in both academic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 52 publications
1
39
0
1
Order By: Relevance
“…This is irrespective of mentor gender. Previous studies have shown that mentors who are members of minoritised groups may be more harsh on fellow group members [56], or put another way, women may be harder on other women [57]. Earlier authors have highlighted that knowledge of the most effective form of mentorship for women in academia is limited [58].…”
Section: Potential Solutionsmentioning
confidence: 99%
“…This is irrespective of mentor gender. Previous studies have shown that mentors who are members of minoritised groups may be more harsh on fellow group members [56], or put another way, women may be harder on other women [57]. Earlier authors have highlighted that knowledge of the most effective form of mentorship for women in academia is limited [58].…”
Section: Potential Solutionsmentioning
confidence: 99%
“…These results are similar to those found in previous research in which age was a relevant factor for the emergence of gender stereotypes, with older adults showing higher gender stereotypes compared to younger adults [ 43 ]. A possible explanation for these results would be that adults live daily in work and personal environments that are characterized by the presence of certain gender stereotypes [ 44 , 45 ], to which the influence exerted by other elements present in everyday life such as the language used [ 46 ] or the information provided by the media must be added [ 47 , 48 ], progressively increasing adults’ perception of gender stereotypes present in all areas, including sport. Another possible explanation would be that male and female teachers with older age and work experience are those who have lived during their childhood and adolescence in a society in which stereotypes were present in all social spheres but were not perceived because they were considered normal at that time.…”
Section: Discussionmentioning
confidence: 99%
“…This decreased number in attendance could contribute to their under-participation in scientific discussions and decreased visibility on a national and international stage. Within the literature, and the daily lived experience of women, it is repeatedly demonstrated that women who self-promote and communicate their work publicly in male-dominated fields often face negative implicit bias [16] and stereotypes such as being labeled "bitchy", seen as lacking "credibility", or judged purely on "appearance" [17]. Due to these daily challenges, women may feel reluctant to speak up in male-dominated environments, and even more so if the male colleagues are older or more senior in the academic/private hierarchy.…”
Section: Plos Onementioning
confidence: 99%